Lambdoid Craniosynostosis: The Relationship with Chiari Deformations and an Analysis of Surgical Outcomes. Issue 3 (March 2016) - Fearon, Jeffrey A.; Dimas, Vanessa; Ditthakasem, Kanlaya
Abstract : Background: A relationship between lambdoid craniosynostosis and Chiari deformations has been suggested, but the true extent of this association remains uncertain. The authors reviewed a single center's experience treating lambdoid synostosis to further elucidate this relationship, examine surgical outcomes, and identify associations that might impact future treatments. Methods: A retrospective chart review was performed of all patients treated for lambdoid craniosynostosis, excluding the syndromic craniosynostoses. Operative data, scans, hospitalization, and subsequent surgical procedures were tracked. All patients were treated with remodeling procedures, but those with Chiari deformations underwent additional simultaneous suboccipital decompressions. Results: Over 22 years, 1006 nonsyndromic craniosynostosis patients were treated, 45 of whom (4.5 percent) presented with lambdoid involvement: 25 single-suture and 20 multiple-suture (complex craniosynostosis). Magnetic resonance imaging revealed that 60 percent of children with unilateral synostosis and 71 percent with a complex synostosis had associated Chiari deformations. The mean surgical age was 12 months, and the average follow-up was 5.7 years: two patients developed syringomyelia requiring transcervical decompressions and two underwent secondary posterior remodeling procedures (one unilateral and one complex synostosis) while undergoing later Chiari decompressions. No patients treated with initial suboccipital decompressions have subsequently developed symptoms requiring treatment. Conclusions: The majority of children with lambdoid synostosis develop Chiari deformations; therefore, routine preoperative and postoperative magnetic resonance imaging should be considered. The treatment of lambdoid craniosynostosis with cranial remodeling procedures, including incontinuity suboccipital decompressions when Chiari deformations were present, was associated with few complications. Ninety-six percent of those with isolated fusions were managed with a single procedure. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.